Tech, smart cities, and regional development in contemporary Russia - Sergi, Bruno S. (Emerald Publishing Limited, 2019)
Russia is one of the world's largest emerging economies. With economic development come technological revolution, growth, and change at every level of society. In Tech, Smart Cities, and Regional Development in Contemporary Russia, editor Bruno S. Sergi brings together expert contributors to explore, and explain, these changes.With chapters on FinTech, the cost of technological growth, and innovation risk management, the contributors grapple with ideas about technology and the intertwined issues that Russia faces in the 21st Century. It includes a wealth of information on today's Russian technological revolution, the overall roles of regional capitals and smart cities, and the role of Russian growth at the regional and international level.Looking across modern Russian development and growth strategies, constraints, and challenges, these chapters follow on from two volumes by the same editor: Exploring the Future of Russia's Economy and Markets: Towards Sustainable Economic Development (2018), and Modeling Economic Growth in Contemporary Russia (2019). Together, the trilogy is essential reading for students and researchers of contemporary international economics, Russian economic affairs, and emerging economies' development.
Prelims -- Chapter 1 The comprehensive plot of socioeconomic development of Russia in the conditions of the technological revolution of the age of globalization -- Chapter 2 Innovational projects of technological growth on the platform of publicprivate partnership: risks and methods of their minimization -- Chapter 3 Standard control of the consumption of material resources as a factor in the technical growth of industrial enterprises -- Chapter 4 Costs and profits of technological growth in Russia -- Chapter 5 Russia's largest regional capitals: the settlement system and the economy of the country -- Chapter 6 Capturing the managerial gap between multinational and domestic companies in Russia: the results of an empirical study 20162017 -- Chapter 7 Russia toward a high-tech development model -- Chapter 8 Modeling regional economic growth in Russia -- Chapter 9 Smart solutions for smart cities: a snapshot of Russian urban life -- Chapter 10 Modeling economic growth for the newly formed countries of the former Soviet Union -- Chapter 11 Modeling Russian industrial, tech, and financial cooperation with the Asia-Pacific region -- Index.
Includes index.
Print version record
Keywords: City planning -- Technological innovations -- Russia; Sustainable development -- Russia; Business & Economics -- Development -- Economic Development; International economics